Development of the KIRASA interactive website for exemplary students of grade IV elementary school - Jenuri; Ani Nur Aeni; Gamal Abdul Nasir Zakaria; Salsa; Ghaida Mufidah Nuha; Irena Okta Berliani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop the KIRASA Interactive Website (Kisah Rasulullah SAW) as an innovative learning medium in Islamic Religious Education to address the challenge of low student engagement in learning Islamic history in the digital era. KIRASA is designed to address the challenges of the current digital era in conveying the history of the Prophet Muhammad SAW's leadership in Medina. The approach used is design and development (D&D) with the ADDIE model. This study involved 17 fourth-grade students and Islamic education teachers from SDN Kadujajar III in Sumedang. This website combines multimedia elements, including digital comics, interactive digital books, an attendance system, a collection of prayers, Word Wall-based interactive games, and various other features that can be accessed anywhere and anytime, or flexibly. The media validation results revealed high feasibility with an average score of 95.6% from experts, which explicitly confirmed that this media met quality standards in terms of material, design, and function. In addition, the positive response rate from students reached 91.5%, indicating that this media was very effective and well-received by the target users. The combination of expert validation results and student responses clearly reinforces the position of the KIRASA Interactive Website as an effective and innovative learning tool. Thus, KIRASA becomes a learning alternative that can improve students' understanding of the leadership of the Prophet Muhammad SAW with a more interesting, interactive, and meaningful learning atmosphere in the classroom.